An Effect Of Surface Roughness To Colour Sensor Detection Range In Ambient Temperature - Abd Samad, Sofian (2018)
An experimental investigation was conducted to explore the effect of surface roughness to colour sensor detection range. The aim of this study is to obtain an acceptable reading level due to colour sensor reading error when there is a difference in surface roughness of the same colour surface. This study uses Arduino Uno microprocessor and is fitted with TCS3200 colour sensor to obtain frequency reading of each ABS plastic colour. The results revealed that the higher the roughness value, the lower the value of the frequency but the higher the colour level will be. The appropriate and acceptable roughness is below 0.38 μm for red coloured plastic red, 0.45 μm for green coloured plastic and 0.35 μm for blue coloured plastic The results presented here may facilitate improvements in the quality of toy manufacture, medical electronic and individuals involved with colour-related studies.